The effect of wearing loupes on upper extremity musculoskeletal disorders among dental hygienists. Issue 3 (26th July 2013) - Hayes, MJ; Osmotherly, PG; Taylor, JA; Smith, DR; Ho, A
Abstract Objectives It is well established that musculoskeletal disorders (MSD) are a significant occupational health issue for dentists and hygienists. Despite this, there has been little advancement in the application of ergonomic principles in the dental profession. While the use of loupes is often promoted as an ergonomic solution, there is little published research to robustly support this claim. The aim of the present study was to investigate the effect of the use of loupes on upper extremity MSD among dental hygienists. Methods The study was conducted using an exploratory pretest and post‐test design, comparing musculoskeletal measures in practising dental hygienists wearing loupes with final‐year dental hygiene students who did not wear loupes. Pre‐ and post‐test measures included valid self‐reported and objective outcome measures and were measured at baseline and 6 months following the intervention. Statistical analysis was conducted as a series of mixed anovas with time and treatment as the independent variables. Results The analysis revealed a significant interaction between time and treatment for the Disabilities of the Shoulder, Arm and Hand (DASH) scores (P < 0.04), indicating an improvement in symptoms for the treatment group but a reversed trend for the controls. There was also a significant mean increase in scapular position measures; however, this finding was evident in both groups, indicating that these were not a result of the intervention. Conclusions Overall, this study suggests that wearing loupes appears to have both positive and negative effects on upper extremity MSD among dental hygienists. Ongoing research is required to determine the long‐term effects of loupes wear, over an extended period of time.